Selected studies in the Slavonic pseudepigrapha - Orlov, Andrei A., 1960- (Studia in Veteris Testamenti Pseudepigrapha, 2009)
This volume is a study of two of the most important Slavonic apocalypses, the Apocalypse of Abraham and 2 Enoch, as crucial conceptual links between the symbolic universes of Second Temple apocalypticism and early Jewish mysticism. The study seeks to understand the mediating role of these Slavonic pseudepigraphical texts in the development of Jewish angelological and theophanic traditions from Second Temple apocalypticism to later Jewish Merkabah mysticism attested in the Hekhalot and Shiʿur Qomah materials. The study shows that mediatorial traditions of the principal angels and the exalted patriarchs and prophets played an important role in facilitating the transition from apocalypticism to early Jewish mysticism.